2000
DOI: 10.1055/s-2000-7547
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Border Necrosis in Skin Flaps of Pigs with Microdialysis

Abstract: Metabolic changes were studied in newly-raised pedicled skin flaps of pigs. These flaps were constructed so that their distal parts were predestined to necrotize. The objective was to find new ways of making early postoperative prognostications about future flap viability. For that purpose, the fluorescein penetration technique was compared with microdialysis monitoring of interstitial tissue concentrations of glucose, lactate, and glycerol. These parameters were measured 6 to 24 hr postoperatively, and collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…In addition, flap tissue oxygenation was stable in both groups. Earlier studies with microdialysis have shown that glucose and lactate concentrations change in a characteristic way when ischemia is present (21)(22)(23). Moreover, Setälä et al (24) have shown in a similar animal model that microdialysis is a sensitive method in the early diagnosis of ischemia in musculocutaneous flaps.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, flap tissue oxygenation was stable in both groups. Earlier studies with microdialysis have shown that glucose and lactate concentrations change in a characteristic way when ischemia is present (21)(22)(23). Moreover, Setälä et al (24) have shown in a similar animal model that microdialysis is a sensitive method in the early diagnosis of ischemia in musculocutaneous flaps.…”
Section: Discussionmentioning
confidence: 94%
“…Microdialysis has been used in experimental and clinical settings for monitoring of energy metabolism in severe brain injury [10], liver transplantation [11], plastic surgery [12], and cardiovascular surgery [13]. An increased lactate-to-pyruvate ratio (L/P ratio) has evolved as a reliable marker for ischemia, and increased glycerol levels as an indicator for cell membrane damage [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Differences between the concentration of the metabolite in the ingoing perfusion solution and that in the outgoing perfusate are determined. The procedure has already reached widespread application in neurosurgery,4,5 neurointensive care, cardiovascular9 and plastic surgery,10 and in the monitoring of skeletal muscle,11,12 adipose tissue, and some metabolic diseases 17. It has also been used in the monitoring of liver grafts in rats …”
Section: Introductionmentioning
confidence: 99%